Insight Into the Roles of Non-coding RNA in Bronchopulmonary Dysplasia - Xi, Yufeng; Wang, Yujia (Frontiers in Medicine, 2021)
Bronchopulmonary dysplasia (BPD) is a chronic lung disease most commonly occurring in premature infants, and its pathological manifestations are alveolar hypoplasia and dysregulation of pulmonary vasculature development. The effective treatment for BPD has not yet been established. Non-coding RNAs, including microRNAs and long non-coding RNAs do not encode proteins, but can perform its biological functions at the RNA level. Non-coding RNAs play an important role in the incidence and development of BPD by regulating the expression of genes related to proliferation, apoptosis, angiogenesis, inflammation and other cell activities of alveolar epithelial cells and vascular endothelial cells. Here we summarize the role of non-coding RNAs in BPD, which provides possible molecular marker and therapeutic target for the diagnosis and treatment of BPD.